PENGARUH PENYULUHAN DENGAN MEDIA DENTAL SPINNING WHEEL GAME TERHADAP PENGETAHUAN TENTANG MAKANAN KARIOGENIK PADA SISWA/I KELAS IV DI SDN 4 GUNTUNG MANGGIS BANJARBARU - Putri, Ayu; Kisworo Utami , Naning; Isnawati, Isnawati; Amperawati, Metty (Poltekkes Kemenkes Banjarmasin, 2025)
The high occurrence of oral health problems is influenced by behaviors that consistently neglect dental and oral health conditions. Particularly, concerning cariogenic foods, children often consume six types of cariogenic foods, namely: candies, chocolate wafers, chocolate bars, chocolate bread, doughnuts, and pudding. Efforts to improve knowledge through education about cariogenic foods can be made. Among the potential strategy that can be used is by using a playful method utilizing the dental spinning wheel game media. This study aims to ascertain the effect of counseling using the dental spinning wheel game media on knowledge about cariogenic foods among fourthgrade students at SDN 4 Guntung Manggis Banjarbaru. The research method used in this study is a quasi-experiment